Mothering by Degrees : Single Mothers and the Pursuit of Postsecondary Education - Duquaine-Watson, Jillian M. (Book collections on Project MUSE., 2017)
"In Mothering by Degrees, I show how single mothers who pursue college degrees in early 21st century America must navigate a difficult course as they attempt to reconcile their identities as single mothers, college students, and, in many cases, employees. As they combine these multiple and often competing roles and responsibilities, they must also negotiate a balance between cultural ideals of motherhood and their own definitions of what it means to be a "good" mother, particularly as those ideals and definitions are shaped within context of post-welfare reform America and the post-secondary institutions they attend. By comparing the experiences of nearly 100 single mother college students attending three postsecondary education institutions in the United States, I illustrate how these women navigate the various obstacles they encounter, especially obstacles related to financial concerns, child care, time constraints, and the "chilly" climate of higher education. In addition, I demonstrate that the women regard postsecondary education not only as a means of escaping poverty but also as an extension of their mothering work, something they do to help ensure the long-term health and well-being of their children. Thus, this project provides a situated, comparative account of the experiences of single mothers who are college students in order to foster a better understanding of the complex ideologies and social structures that influence the life choices and education experiences of members of this important but understudied student population. Finally, the project discusses policies and programs that can help provide better support to single mother and may diminish the challenges they face as they endeavor to complete their education"--